Cooking the Thai way : culturally authentic foods, including low-fat and vegetarian recipes / Supenn Harrison; Judy Monroe Peterson - Harrison, Supenn
An introduction to the cooking of Thailand including such recipes as lemon chicken soup, satay, and Thai spring rolls. Also includes information on the history, geography, customs, and people of Thailand.